Nivel de satisfacción del curso en línea ¨Origen fetal de enfermedades del adulto¨ - Daniel Quintana Hernández; Roberto Lardoeyt Ferrer; Ana Duadys Pérez Álvarez; Yanisbell Fajardo Peña (Medimay)
Introducción: